An Analytical Review of the State of Car Insurance in Algeria During the Period 2013-2022 - Mossab Bali, Bourin hanachi (European Economic Letters (EEL), 2024)
This study aims to examine the state of car insurance in Algeria by exploring the legal and economic frameworks that regulate this insurance sector. It also analyzes statistics and figures for this sector, delving into the reasons why it holds the largest share of premiums underwritten by insurance companies compared to other branches of insurance. The study adopts a descriptive and analytical methodology, focusing on various concepts related to car insurance and highlighting its economic and social roles. This is achieved by examining production statistics and compensation payouts within this sector for the period 2013-2022. The analysis of car insurance sector statistics revealed that it accounted for a significant portion, nearly half, of the total insurance production in most years of the study. This dominance is attributed to the mandatory nature of civil liability insurance for vehicles and the substantial insurance base, represented by the large national fleet of cars. Additionally, there has been a growth in the volume of compensation payouts due to the high number of traffic accidents, which exceeded 60,000 annually.